Neutralization of antibody-enhanced dengue infection by VIS513, a pan serotype reactive monoclonal antibody targeting domain III of the dengue E protein. - Yadunanda Budigi; Eugenia Z Ong; Luke N Robinson; Li Ching Ong; Kirk J Rowley; Alexander Winnett; Hwee Cheng Tan; Sven Hobbie; Zachary Shriver; Gregory J Babcock; Sylvie Alonso; Eng Eong Ooi (Public Library of Science (PLoS), 2018)
Dengue virus (DENV) infection imposes enormous health and economic burden worldwide with no approved treatment. Several small molecules, including lovastatin, celgosivir, balapiravir and chloroquine have been tested for potential anti-dengue activity in clinical trials; none of these have demonstrated a protective effect. Recently, based on identification and characterization of cross-serotype neutralizing antibodies, there is increasing attention on the potential for dengue immunotherapy. Here, we tested the ability of VIS513, an engineered cross-neutralizing humanized antibody targeting the DENV E protein domain III, to overcome antibody-enhanced infection and high but brief viremia, which are commonly encountered in dengue patients, in various in vitro and in vivo models. We observed that VIS513 efficiently neutralizes DENV at clinically relevant viral loads or in the presence of enhancing levels of DENV immune sera. Single therapeutic administration of VIS513 in mouse models of primary infection or lethal secondary antibody-enhanced infection, reduces DENV titers and protects from lethal infection. Finally, VIS513 administration does not readily lead to resistance, either in cell culture systems or in animal models of dengue infection. The findings suggest that rapid viral reduction during acute DENV infection with a monoclonal antibody is feasible.